Turn coat : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2010)
When he is accused of treason against the Wizards of the White Council, Warden Morgan goes in search of Harry Dresden in a desperate attempt to clear his name and stop the deadly punishment from taking place.